Potential of Ethanol Extract of Forest Clove Leaves (Syzygium Obtusifolium L.) As A Biolarvacide on The Mortality Of The Dengue Fever Vector Aedes Aegypti - Mustakim Rumasukun; Maria Nindatu; Martha Kaihena; Hery Jotlely (Agrologia, 2022)
The content of eugenol forest clove (Syzygium obtusifolium L.) have the ability as a natural larvacidal agent, in addition to saponins and flavonoids these compounds can affect the digestive system of Aedes aegypti larvae so that the larvae experience stomach poisoning which results in the death of the larvae. The aim of the study was to determine the effectiveness, effective concentration, and determine the LC50 of ethanol extract of forest clove leaves as a biolarvasidal against the mortality of Aedes aegypti mosquito larvae. The type of research is a laboratory experiment, the research is carried out in the Laboratory of Parasitology, Department of Biology, Faculty of Natural Science Pattimura University. The study used a completely randomized design (CRD). The results were analyzed by Analysis of Variance using the SPSS IBM 24.00 program. The results showed that the ethanol extract of forest clove leaves as a biolarvaside against the mortality of Aedes aegypti mosquito larvae because the administration of ethanolic extract of forest clove leaves with each different concentration can kill with a concencentration of 0,3% effective as biolarvasidal of Aedes aegypti larvae and the LC50 value 0f 0,01 % prospectively development as a biolarvaside